Neutrino oscillation anomalies - Ternes Christoph Andreas (EPJ Web of Conferences, 2023)
I give an overview of some of the several anomalies appearing in neutrino oscillation experiments, setting particular focus to the reactor antineutrino anomaly and the Gallium anomaly. I will discuss these two anomalies in some detail and, in particular, compare their explanation due to neutrino oscillations in presence of a light sterile neutrino among each other and also with the bounds from the analyses of reactor spectral ratio data, β-decay data, and solar neutrino data.